Changes in primary care prescribing patterns for paediatric asthma: a prescribing database analysis. Issue 6 (19th May 2011) - Elkout, Hajer; Helms, Peter J; Simpson, Colin R; McLay, James S
Abstract : Background: Little is known about the impact of British asthma management guideline revisions. Concerns about the use of high dose inhaled corticosteroids (ICS) in children have resulted in the promotion of add-on therapy. Aims: To assess prescribing patterns of asthma medication in children in the primary care setting. Methods: Retrospective observational study of asthma prescribing in children aged 0-18 years using primary care database from 2001 to 2006. Results: The proportion of children prescribed oral corticosteroids increased significantly (from 6% in 2001-2002 to 16% in 2005-2006, p<0.001), while the proportion of children prescribed an ICS dose of >400 mcg decreased from 16.2% to 11.7% (P<0.001). The proportion of children prescribed an add-on therapy and an ICS dose >400 µg, increased from 38.8 % in 2001-2002 to 61.2% in 2005-2006 (p<0.001). Conclusions: Although adherence with asthma management guidelines is not optimal, this study has identified improved adherence in primary care.